Comparison of Short-Term Clinical Outcome in In-Hospital Patients of ST Elevation versus Non ST Elevation Myocardial Infarction - Rahman, Aparna; Khan, MM Zahurul Alam; Alam, Md Zahid; Hoque, Shabnam Jahan; Khan, Tunaggina Afrin; Hossain, Mohammad Shakhawat (Bangladesh Heart Journal, 2017)
Objective: To compare short term clinical outcome in hospital patient of ST Elevation versus Non ST Elevation Myocardial Infarction. Methodology: This cross sectional observational study was carried out enrolling 100 subjects with ST elevation and Non ST elevation Myocardial Infarction, in the Department of Cardiology, BIRDEM General Hospital, Shahbagh, Dhaka, over a period of six months from January 2012 to June 2012. Results: Mean age and gender difference was significant between STEMI and non-STEMI. Most common short term clinical outcome was heart failure (80.95% vs 75.68%). Atrial fibrillation was observed in (4.76% vs 3.44%), VT(2.38% vs 1.72%), cardiogenic shock (31.03% vs 17.24%), hypotension (76.19% vs 58.62%), reinfarction (2.38% vs 00%) and death (14.28% vs 5.17%) were observed among ST and Non ST elevation MI respectively. Statistical analysis revealed that all the parameters of short term outcome had significant difference except atrial fibrillation and VT. Conclusion: It could be concluded that short term outcome were relatively worse in ST elevated MI and to be managed with all possible therapeutic modules. Bangladesh Heart Journal 2016; 31(2) : 70-74